(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: Seasonal variation in the hospital admission of cardiac patients has been widely reported. However, limited data on Bangladesh is available regarding this matter. The aim of the current study was to investigate the effect of seasonal variation on hospital admission of cardiac patients in Cardiology Department of Chittagong Medical College Hospital. Materials and methods: Over a period of two years (From April 2016 to March 2018) the number of patients hospitalized due to various cardiac ailements and number of death among these hospitalized patients were recorded on a day-to-day basis. The data were recorded according to the chief reason of hospital admission such as acute myocardial infarction (STEMI, NSTEMI) Unstable Angina (UA) Heart failure, cardiomyopathy (Ischemic and Dilated) arrhythmia. The data were cumulated and analyzed on month-wise and season-wise manner. Results: A total of 22985 patients were admitted over the study period.13408 were male and 9577 were female, M/F ratio 1.4:1). The highest number of patients were admitted during winter 7375(32.08%) and lowest during summer 4623 (20.11%). The hospital admission was also significantly higher in winter compared to other seasons. Acute MI (n = 2374) acute LVF (n = 1582) and UA (n = 1277) were the top three reasons for hospitalization. Number of death also significantly higher in winter compared to other seasons. Conclusion: A seasonal variation in the hospital admission due to CVDs with a peak in winter was clearly demonstrated in the study. These data could be useful to improve causative prevention measures, therapeutic management and educational strategies. JCMCTA 2020 ; 31 (2) : 122-126